Relationship Between the Pyroptosis Pathway and Epilepsy: A Bioinformatic Analysis - Xia, Lu; Liu, Lu; Wang, Qiang; Ding, Jing; Wang, Xin (Frontiers in Neurology, 2022)
Purpose: This study aimed to analyse the correlation between the pyroptosis pathway and epilepsy using bioinformatics analysis technology. We analysed the expression of gasdermin D (GSDMD), a key molecule of pyroptosis, in kainic acid-induced epileptic mice. Methods: Weighted gene co-expression network analysis (WGCNA) was used to construct a signed co-expression network from expression data to screen gene sets closely related to epilepsy. The correlation between the module and epilepsy was verified through module conservative analysis, gene ontology (GO) annotation analysis, and correlation analysis with known epilepsy genes. We obtained currently recognised pyroptosis-related molecules through literature review, and correlation analysis was used to evaluate their correlation with epilepsy. Differentially expressed gene (DEG) analysis was used to analyse expression changes of pyroptosis-related molecules at the transcriptome level, compared to the control. We subsequently established a kainic acid-induced status epilepticus (SE) model in mice and validated the mRNA and protein expression of GSDMD, the key molecule of pyroptosis, by quantitative reverse transcription PCR (qRT-PCR) and western blotting (WB). Results: Using WGCNA, module conservative analysis, and correlation analysis with known epilepsy genes, we screened out a module (a gene set of interest) closely related to epilepsy that was prominently enriched in immune and inflammatory-related biological processes. Correlation analysis results suggest that pyroptosis-related molecules are closely related to this module, but have no obvious correlation with others. DEG analysis of molecules associated with pyroptosis suggests that most of the pyroptosis-related molecules had significantly increased expression after SE, such as IL1b, Casp1, Casp4, Pycard, Gsdmd, Nlrp3, Aim2, Mefv, Tlr2, Tlr3, and Tlr4. qRT-PCR and WB analysis confirmed that the mRNA and protein levels of GSDMD in the mouse hippocampus were significantly upregulated after SE. Conclusions: Our study highlights that the pyroptosis pathway may be closely related to epilepsy. GSDMD, as the key executive molecule of pyroptosis, will help to understand the pathogenesis of epilepsy and aid in discovering new targets for anti-epileptic drug treatments.